Pursuing healthy homeownership: an evaluation of the neighborhood health trajectories of shared equity homeowners - Geoffrey M. Gusoff; Alex Ramiller; Arthur Acolin; Ruoniu Wang; Frederick J. Zimmerman (BMC Public Health)
Abstract Background Shared equity homeownership – a model in which low- and moderate-income households purchase homes at affordable prices on the condition that the houses remain affordable upon resale – has been shown to produce several health-enhancing housing outcomes. These include permanent affordability, housing stability, and modest wealth-building. However, studies suggest low- and moderate-income households may sacrifice neighborhood quality when becoming homeowners, which can undermine the health benefits of homeownership. To understand the health impacts of the shared equity homeownership model more fully, it is important to evaluate participants’ neighborhood health trajectories – how their neighborhood health environments change when they move into homeownership – and how these trajectories compare to those of similar households entering traditional homeownership and those continuing to rent. Methods We conducted difference-in-differences analyses comparing changes in neighborhood health characteristics (walkability, food access, socio-economic vulnerability, and life expectancy) for US households moving into shared equity homeownership between 1997 and 2017 compared to households moving into traditional homeownership and those continuing to rent. Shared equity homeowner data was obtained through the Grounded Solutions Network HomeKeeper National Data Hub and households from the Panel Study of Income Dynamics served as matched controls for the analysis. All data on neighborhood characteristics were obtained from publicly available, census tract-level datasets. Results Compared to households entering traditional homeownership, households entering shared equity homeownership experienced a relative increase in walkability (difference-in-differences 1.07, p = 0.004), increase in food access (0.13, p < 0.001), increase in socio-economic vulnerability (0.06, p = 0.02), and similar life expectancy. Compared to households moving between rental units, households entering shared equity homeownership experienced similar trajectories in terms of walkability and food access but experienced a relative increase in socio-economic vulnerability (0.06, p = 0.01) and decrease in average neighborhood life expectancy (-0.64, p = 0.01). Conclusions Households entering shared equity homeownership avoid the sacrifices in neighborhood walkability and food access that are associated with moving into traditional homeownership, but they experience increased neighborhood socio-economic vulnerability. While understanding the net impact of these factors on individual and household health requires further study, these results can inform the siting and design of shared equity homeownership units to maximize the health benefits of the model.